Comparative study of Equine Chorionic Gonadotropine and Licorice Extract (Glycyrrhiza Glabra) on the some Reproductive Traits in Awassi Ram Lambs - Al-Shammary, Salah M.; Al-Timimi, Ihsan H.; Al-Ani, Ahmad A. (The Iraqi Journal of Veterinary Medicine, 2013)
This study was conducted to find out the effect of licorice extract and eCG on the some reproductive traits in Awassi ram lambs. This study was conducted on State Board for Agriculture Researches, Animal Researches station. Twenty four Awassi ram lambs at the age of 67-77 days were randomly divided into four groups according to the lambing date as follow: Group (A) was injected with eCG 300 I.U /lamb/week. Group (B) was treated with licorice 300 mg/kg B.W/week orally. Group(C) also was treated licorice 400 mg/kg B.W/week orally. Group (D) were kept as acontrol group. Testes measurements were taken at the 12th week of the study period. The level of testosterone hormone was measured at monthly intervals. Age of puberty, number of mounts/successful ejaculation were recorded. Testes measurements length and depth of right and left of animal in groups B and C showed significantly (P< 0.05) higher values than the control and group A. Width of the right and left testes of lambs in all groups did not record significant differences. Circumferences of the testes showed higher (P< 0.05) values in group B compared to other groups. Serum testosterone concentration increased in all animals during the experimental periods but group B and C showed significantly (P< 0.05) higher values than other groups. Age of puberty and sperm production of the lambs in the control group showed significantly (P < 0.05) higher values compared with all groups, but group A recorded significantly (P< 0.05) higher values compared with groups B and C, while groups B and C recorded significantly (P< 0.05) lower age of puberty compared with groups A and control. The number of Mounts/successful ejaculate decreased with progress of age in all groups, while the control group recorded significantly (P< 0.05) higher number than other treated groups. Group B recorded significantly (P< 0.05) lower values than A and C groups.